Characterization and Functional Studies of a Novel Depolymerase Against K19-Type Klebsiella pneumoniae - Hua, Yunfen; Wu, Yongqin; Guo, Minjie; Ma, Ruijing; Li, Qingchuan; Hu, Zheyuan; Chen, Hongrui; Zhang, Xingyu; Li, Hui; Li, Qingtian; He, Ping (Frontiers in Microbiology, 2022)
Carbapenem-resistant Klebsiella pneumoniae (CRKP), a pathogen that causes severe nosocomial infections and yields a high mortality rate, poses a serious threat to global public health due to its high antimicrobial resistance. Bacteriophages encode polysaccharide-degrading enzymes referred to as depolymerases that cleave the capsular polysaccharide (CPS), one of the main virulence factors of K. pneumoniae. In this study, we identified and characterized a new capsule depolymerase K19-Dpo41 from K. pneumoniae bacteriophage SH-KP156570. Our characterization of K19-Dpo41 demonstrated that this depolymerase showed specific activities against K19-type K. pneumoniae. K19-Dpo41-mediated treatments promoted the sensitivity of a multidrug-resistant K19-type K. pneumoniae strain to the bactericidal effect of human serum and significantly increased the survival rate of Galleria mellonella infected with K19-type K. pneumoniae. Our results provided strong primary evidence that K19-Dpo41 was not only effective in capsular typing of K19-type K. pneumoniae but promising in terms of developing new alternative therapeutic strategies against K19-type CRKP infections in the future.